2022
DOI: 10.3390/ijms23179643
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-99b-5p and Upregulation of Nuclear mTOR Cooperatively Promotes the Tumor Aggressiveness and Drug Resistance in African American Prostate Cancer

Abstract: Mammalian target of rapamycin (mTOR) regulates various fundamental cellular events including cell proliferation, protein synthesis, metabolism, apoptosis, and autophagy. Tumor suppressive miR-99b-5p has been implicated in regulating PI3K/AKT/mTOR signaling in a variety of types of cancer. Our previous study suggested the reciprocal miR-99b-5p/MTOR (downregulated/upregulated) pairing as a key microRNA-mRNA regulatory component involved in the prostate cancer (PCa) disparities. In this study, we further validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Indeed, a significant reduction in nuclear mTOR and androgen receptor (AR) has been detected, targeting the AR-mTOR axis using miR-99b-5p. This finding suggests that miR-99b-5p is a novel potential therapeutic target in this type of cancer [27]. Other cancers such as glioblastoma [28], lung [29], multiple myeloma [30] and lymphomas [31] are additionally characterized by PI3K/Akt/mTOR alterations.…”
Section: Pi3k/akt/mtor Activation In Cancermentioning
confidence: 92%
“…Indeed, a significant reduction in nuclear mTOR and androgen receptor (AR) has been detected, targeting the AR-mTOR axis using miR-99b-5p. This finding suggests that miR-99b-5p is a novel potential therapeutic target in this type of cancer [27]. Other cancers such as glioblastoma [28], lung [29], multiple myeloma [30] and lymphomas [31] are additionally characterized by PI3K/Akt/mTOR alterations.…”
Section: Pi3k/akt/mtor Activation In Cancermentioning
confidence: 92%
“…The protocol for IHC assay was adapted/modified from our previous studies ( 34 , 35 ). Briefly, TMA slides were first deparaffinized in xylene, followed by immersion in xylene/alcohol (1:1) solution and rehydrated through graded alcohols (100%, 95%, 70% and 50% of alcohol, respectively) to distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…IHC images were captured using Pannormic Midi Digital Scanner (3DHISTECH Ltd., Budapest, Hungary) and visualized using CaseViewer program (3DHISTECH, Budapest, Hungary). The analysis and quantification of IHC images were performed using ImageJ software (NIH, Bethesda, MD, USA), as described in our previous study ( 34 ). The statistical analysis was performed using ANOVA with Tukey’s post-hoc test for the multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…The issue of tumor resistance to drugs is further highlighted in a study by Gujrati et al [ 7 ], which was conducted in African American men with prostate cancer. The nuclear mammalian target of rapamycin (mTOR) is known to regulate cell proliferation, protein synthesis, metabolism, apoptosis, and autophagy [ 8 ], and was shown to be elevated in patients with prostate cancer as well as other advanced cancers (lung, breast, and colon).…”
mentioning
confidence: 99%
“…The nuclear mammalian target of rapamycin (mTOR) is known to regulate cell proliferation, protein synthesis, metabolism, apoptosis, and autophagy [ 8 ], and was shown to be elevated in patients with prostate cancer as well as other advanced cancers (lung, breast, and colon). The dysregulation of microRNA, specifically microRNA-99b-5p, is known to be linked with prostate cancer [ 9 ], and in the study by Gujrati et al [ 7 ] it was found to be downregulated. These investigators went on to demonstrate, in vitro, that transfection with microRNA-99b-5p significantly reduced the expression levels of nuclear mTOR and androgen receptor (AR).…”
mentioning
confidence: 99%